Bentuk Penyajian Tari Sambut Muara Enim Di Sanggar Belide Kabupaten Muara Enim - Tiara Wulandari; A. Heryanto; Nofroza Yelli (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
The Muara EnimWelcom Dance is a traditional dance in Muara Enim Regency, the welcome dance is still developing today. The aim of this research is to describe the form of presentation of the welcome dance. To strengthen the research, the research interviewed 3 informants Dian PermanaJoeliusS.Pd, Elani DestiaristaS.Pd, Sri WulandariS.Pd, people who had received information about the welcome dance, from its presentation to how the welcome dance works displayed. The benefits of this research are to preserve existing arts, and it is hoped that it will be useful for: increasing the insiht of researchers and readers of this article, to know what the Muara Enim welcome dance is, for similar researchers so that it can be used as a reference. This research uses qualitative methods, data collection and retrieval techningques using observation, interviews and documentation techniques. The results of this researchis that the welcome dance is a form of presentation consisting of dancer are walking on tiptoe, hands stacked, opening right and left, praying up, picking right and left up. The music used in the welcoming dance includes drums, kromongan, simbal and gong. The make-up used by dancers for female dancers uses beautiful make-up while male dancers use handsome make-up. The costumes for the welcoming dance are clothes brackets, songketclosth, shawls, paksangko crowns, potpourri of flowers. The floor design is in the shape of the letter V and has straight horizontal and vertical lines. The property used by dancers of tanggai, betel taps, umbrellas and spears. The performance venue is like a performance stage in general.